2010
DOI: 10.1002/col.20582
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on vermilion, gingiva, and tooth color of young Uygur and Han populations in Xinjiang, China

Abstract: This study examines oral tissue color in Uygur and Han Chinese populations. The color of oral tissues is of great significance in dental field. It remains uncertain whether there is any difference in the color of oral tissues between different nationalities or ethnicities. Little is known about the color of oral tissues in different Chinese populations. The study included 263 Uygur and Han students aged 18-22 years. The color of anterior teeth, vermilion, and attached gingiva in the subjects was measured by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The color of human gingiva has been evaluated using the visual method and different color measuring instruments, including colorimeters, spectrophotometers, and spectroradiometers . Recently, a comprehensive report on color range and color distribution of healthy human gingiva included data for age, gender and ethnicity, and varied cohorts and found that ethnicity and age had significant influence on the color characteristics of gingiva …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The color of human gingiva has been evaluated using the visual method and different color measuring instruments, including colorimeters, spectrophotometers, and spectroradiometers . Recently, a comprehensive report on color range and color distribution of healthy human gingiva included data for age, gender and ethnicity, and varied cohorts and found that ethnicity and age had significant influence on the color characteristics of gingiva …”
Section: Introductionmentioning
confidence: 99%
“…The color of human gingiva has been evaluated using the visual method [1][2][3] and different color measuring instruments, including colorimeters, spectrophotometers, and spectroradiometers. [4][5][6][7][8][9][10] Recently, a comprehensive report on color range and color distribution of healthy human gingiva included data for age, gender and ethnicity, and varied cohorts and found that ethnicity and age had significant influence on the color characteristics of gingiva. 11 Limited information on the fundamental optical properties of human gingiva, its polychromatic nature, and the imperfections of existing gingival shade guides just add to the complexity of the topic.…”
Section: Introductionmentioning
confidence: 99%